2019
DOI: 10.1253/circj.cj-18-1391
|View full text |Cite
|
Sign up to set email alerts
|

Withaferin A Prevents Myocardial Ischemia/Reperfusion Injury by Upregulating AMP-Activated Protein Kinase-Dependent B-Cell Lymphoma2 Signaling

Abstract: Background: Withaferin A (WFA), an anticancer constituent of the plant Withania somnifera, inhibits tumor growth in association with apoptosis induction. However, the potential role of WFA in the cardiovascular system is little-studied and controversial. Methods and Results: Two different doses of WFA were tested to determine their cardioprotective effects in myocardial ischemia/ reperfusion (MI/R) injury through evaluation of cardiofunction in wild-type and AMP-activated protein kinase domain negative (AMPK-D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Many studies have demonstrated effect of WFA on apoptosis of cardiomyocytes [ 63 ]. Our previous work have shown that WFA attenuated skeletal muscle cachexia [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated effect of WFA on apoptosis of cardiomyocytes [ 63 ]. Our previous work have shown that WFA attenuated skeletal muscle cachexia [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Withaferin A also acts on cellular pathways, such as cell cycle arrest [ 296 , 297 ], inhibits apoptosis via activated Akt-mediated inhibition of oxidative stress and ROS-dependent mitochondrial dysfunction in human colorectal cancer cells [ 298 , 299 ], and inhibits endoplasmic reticulum stress-associated apoptosis [ 300 ]. Low doses of withaferin A are cardioprotective in ischemia/reperfusion events via upregulation of the antiapoptotic mitochondrial pathway in an AMPK-dependent manner [ 301 ]. Another group of recently-synthetized inhibitors of TASK-3 channel activity is the 5,6,7,8-tetrahydropyrido [4,3-d]pyrimidine (THPP)-derived compounds IN-THPP and mitoIN-THPP, which differs by the addition of a triphenylphosphonium (TPP) group [ 294 ].…”
Section: Modulators Of Mitochondrial Task Channelsmentioning
confidence: 99%
“…In cancer cells, where the basal ROS levels are already relatively high, WA is able to further increase oxidative stress and promote cell death [ 90 , 91 ]. This is in stark contrast with the chronic inflammatory disease setting, where WA attenuates oxidative stress and suppresses ROS production, thereby decreasing disease severity [ 56 , 60 , 92 , 93 ]. This suppression is often mediated by activation of the anti-inflammatory Nrf2 pathway, which inhibits several inflammatory mediators and enzymes and activates antioxidant target genes [ 94 ].…”
Section: Molecular Targets Of Withaferin a In The Inflammatory Resmentioning
confidence: 99%